The Theory Model and Solution of the Wall Jet of Platform Piston Wind - Wang Lihui; Wang Wei; Du Xiaoming; Li Zhiling; Sun Yunlei; Jiang Xin (Zhileng xuebao)
The platform piston wind is defined firstly. Then, the wall jet theory of the platform piston wind is put forward. Through the mathematical modeling, the initial segment and main section theoretical model of the platform piston wind is built up. The initial segment is divided into boundary layer area, potential flow core area and free shear zone. The main section is composed of boundary layer area and free shear zone. The typical point velocity dynamic characteristics and the typical section velocity distribution in the vertical wall direction both in the initial segment and main section are obtained based on the theoretical expression solution and numerical simulation. The results of the above two methods coincide each other. The theoretical results are verified by the field measurement.